2012
DOI: 10.7251/ssh1201022b
|View full text |Cite
|
Sign up to set email alerts
|

Globalne kvantitativne promjene bazičnih i situaciono-motoričkih sposobnosti pod uticajem programa odbojke

Abstract: Istraživanje je sprovedeno na uzorku od 73 učenika sedmih i osmih razreda Osnovne škole „Tojšići“ koji su u sklopu dodatne nastave realizovali precizno definisani program odbojke. U istraživanju je primijenjeno 15 varijabli za procjenu bazičnih motoričkih sposobnosti i 5 varijabli za procjenu situaciono-motoričkih sposobnosti iz odbojke.Osnovni cilj istraživanja bio je da se utvrde globalne kvantitativne promjene bazičnih motoričkih i situaciono-motoričkih sposobnosti pod uticajem tromjesečnog eksperimentalnog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
3
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 0 publications
3
3
0
2
Order By: Relevance
“…Moreover, Nešič et al [23] showed certain improvements in the general and specific motor skills (volleyball skills) after three months of applied volleyball practice. Similar results were obtained in PE classes following a precisely defined volleyball program of techniques and tactics [24]. The authors found statistically significant changes in the volleyball technique, and the most significant changes occurred in the tests of serving preci-…”
Section: Discussionsupporting
confidence: 69%
“…Moreover, Nešič et al [23] showed certain improvements in the general and specific motor skills (volleyball skills) after three months of applied volleyball practice. Similar results were obtained in PE classes following a precisely defined volleyball program of techniques and tactics [24]. The authors found statistically significant changes in the volleyball technique, and the most significant changes occurred in the tests of serving preci-…”
Section: Discussionsupporting
confidence: 69%
“…To what extent the curriculum content will show better effects, should be seen through the application of other programmes of curriculum content. Many previous studies in the field of physical and health culture (Badrić, 2010;Badrić et al, 2015;Badrić & Gašparić Baniček, 2016;Bajrić, O., Šmigalović, Bašinac, & Bajrić, S., 2012;Bajrić, Šmigalović, Bašinac, & Bilić, 2012;Borčić et al, 2005;Džibrić et al, 2009;Ferhatbegović et al, 2010;Hodžić, 2008;Milenković et al, 2011;Rađo et al, 2003;Selmanović et al, 2008) have shown that effects on the changes in anthropological characteristics of students are greater and more significant when regular classes are combined with additional organizational forms of work in primary and secondary schools (extracurricular and out-of-school activities, elective activities, various forms of supplementary education, school sports societies and other).…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Ljubojević et al (2011), basketball content has shown to have positive effects on the development of all the motor skills of boys on a smaller scale and of girls on a larger scale. In numerous studies (Bajrić et al, 2012;Korjenić et al, 2012;Šmigalović et al, 2012;Nešić et al, 2013), the authors applied content from volleyball and obtained results that showed positive effects on the development of basic motor skills and situational motor skills. Sozen (2012) managed to induce positive changes of agility and flexibility in girls by conducting volleyball training as an additional activity in physical education.…”
Section: Discussionmentioning
confidence: 99%